2009
DOI: 10.1038/onc.2008.496
|View full text |Cite
|
Sign up to set email alerts
|

Runx3 expression in gastrointestinal tract epithelium: resolving the controversy

Abstract: We reported earlier that RUNX3 is expressed in human and mouse gastrointestinal tract (GIT) epithelium and that it functions as a tumor suppressor in gastric and colorectal tissues. However, there have been conflicting reports describing the absence of Runx3 in GIT epithelial cells. A part of the controversy may be derived from the use of a specific antibody by other groups (referred to as G-poly). Here, we show further evidence to support our earlier observations and provide a possible explanation for this ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
3
24
0
Order By: Relevance
“…We thus concluded that RUNX3 is a gastric tumor suppressor gene that controls the growth, apoptosis, and differentiation of gastric epithelial cells [17][18][19][20] . Recently, RUNX3…”
Section: Introductionmentioning
confidence: 82%
“…We thus concluded that RUNX3 is a gastric tumor suppressor gene that controls the growth, apoptosis, and differentiation of gastric epithelial cells [17][18][19][20] . Recently, RUNX3…”
Section: Introductionmentioning
confidence: 82%
“…As the opposing viewpoints have already been discussed elsewhere, the reader is advised to refer to the respective publications (Bae and Ito, 2003;Levanon et al, 2003;Ito et al, 2009;Levanon and Groner, 2009). We anticipate that this controversy will soon be resolved with further in-depth studies.…”
Section: Controversy On Runx3 Expression In Gastrointestinal Tract Epmentioning
confidence: 98%
“…For example, Runx3-null balb/c mice can survive until adulthood , whereas FVB and C57BL/6 mice carrying the same Runx3 mutant allele die soon after birth (Ito et al, 2008). Differences in the gene targeting strategies could also explain the differences (Ito et al, 2009).…”
Section: Runx3 Insufficiency Leads To the Onset Of Lung Adenomas In Micementioning
confidence: 99%